Association between ambient PM2·5 and under-5, infant, and child mortality in Latin America, 2010–15: a longitudinal analysis. (April 2021) - Ortigoza, Ana; Gouveia, Nelson; Kephart, Josiah; Prado-Galbarro, Francisco; Friche, Amelia A; Sanchez, Brisa N; Diez-Roux, Ana V
Abstract: Background: Highly urbanised and rapidly urbanising countries are facing critical air pollution problems. In Latin American cities, the effect of ambient PM2·5 on child health has not been extensively explored. We examined associations between ambient PM2·5 and under-5 mortality (deaths in those younger than 5 years per 1000 livebirths) infant mortality (deaths in those younger than 1 year per 1000 livebirths), and child mortality (deaths in those aged 1–4 years per 10 000 children) in Latin American cities. Methods: In this longitudinal analysis, we estimated under-5 mortality, infant mortality, and child mortality for the period Jan 1, 2010, to dec 12, 2015, for 1152 subcity units clustered in 337 cities in Argentina, Brazil, Chile, Colombia, Costa Rica, Guatemala, and Mexico. We retrieved mean annual PM2·5 for each subcity unit. Using linear mixed-effects models, we estimated the percentage change in under-5 mortality, infant mortality, and child mortality associated with a 1 μg/m 3 increase in annual PM2·5, adjusted for city-level and subcity-level predictors (population growth, gross domestic product, living conditions, water and sanitation provision, population education, and mass transit availability). Findings: Over the study period, mean annual PM2·5 was 12·7 μg/m 3 (SD 6·3), under-5 mortality was 14·2 deaths per 1000 livebirths, infant mortality was 12·1 deaths per 1000 livebirths, and child mortality was 4·8 deaths per 10 000 children. A 1 μg/m 3 annual increase in PM2·5 was associated with 0·4% (95% CI 0·1 to 0·7) increase in under-5 mortality and 0·5% (95% CI 0·2 to 0·9) increase in infant mortality We found no significant association between PM2·5 increases and changes in child mortality (–0·1% [95% CI −0·8 to 0·6]). Interpretation: Our findings support the need for environmental protection in the Latin American region for improving both planetary and population health. Transdisciplinary strategies at local levels, including public health practitioners and policy stakeholders involved in urban development, are key for implementing these changes. Funding: The Wellcome Trust initiative Our Planet, Our Health.